Digital Media Influence on Adolescents’ Behavior during the COVID-19 Pandemic: Self-Intravenous Injection of Lactobacilli Drinking Yogurt - Koh, Eunjung; Choi, Insu; Choi, Seul-A; Kang, Yeo-Jin; Cho, Hwa-Jin (Children (Basel), 2022)
During the coronavirus disease 2019 (COVID-19) pandemic, widened physical distance and social deprivation are being replaced with digital media use. The media’s social function has tremendously increased following the COVID-19 era and adolescents living in a media-saturated world are the most vulnerable subjects of all. Social media use can encourage risky behavior in adolescents. Posting videos related to risk behaviors on social media has been linked to jeopardizing not only mental health but also physical safety. Herein, we report a case of a 12-year-old boy who intravenously self-injected Lactobacilli drinking yogurt for the purpose of filming a video to post on social media. He was treated with antibiotics based on Lactobacilli sepsis that cured him without any complications. In order to reduce the risk-taking behavior of adolescents, social norms need to be straightened up, and the social responsibility of hosts is strongly recommended.